FOXP3 and GATA3 Polymorphisms, Vitamin D3 and Multiple Sclerosis - Concetta Scazzone; Luisa Agnello; Bruna Lo Sasso; Giuseppe Salemi; Caterina Maria Gambino; Paolo Ragonese; Giuseppina Candore; Anna Maria Ciaccio; Rosaria Vincenza Giglio; Giulia Bivona; Matteo Vidali; Marcello Ciaccio (Brain Sciences, 2021)
Background: Regulatory T cells (Tregs) alterations have been implicated in the pathogenesis of Multiple Sclerosis (MS). Recently, a crucial role of the X-Linked Forkhead Box P3 (FoxP3) for the development and the stability of Tregs has emerged, and FOXP3 gene polymorphisms have been associated with the susceptibility to autoimmune diseases. The expression of Foxp3 in Tregs is regulated by the transcription factor GATA binding-protein 3 (GATA3) and vitamin D3. The aim of this retrospective case-control study was to investigate the potential association between FOXP3 and GATA3 genetic variants, Vitamin D3, and MS risk. Methods: We analyzed two polymorphisms in the FOXP3 gene (rs3761547 and rs3761548) and a polymorphism in the GATA3 gene (rs3824662) in 106 MS patients and 113 healthy controls. Serum 25(OH)D3 was also measured in all participants. Results: No statistically significant genotypic and allelic differences were found in the distribution of FOXP3 rs3761547 and rs3761548, or GATA3 rs3824662 in the MS patients, compared with controls. Patients that were homozygous for rs3761547 had lower 25(OH)D3 levels. Conclusions: Our findings did not show any association among FOXP3 and GATA3 SNPs, vitamin D3, and MS susceptibility.